SPE Europec Featured at 80th EAGE Conference and Exhibition 2018
DOI: 10.2118/190862-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clean-Up Efficiency of Multiple Fractured Horizontal Wells and Hydraulically Fractured Vertical Wells in Tight Gas Reservoirs

Abstract: Hydraulic fracturing is a well-established stimulation technique especially for unconventional reservoirs. However, sometimes its performance is less than expected due to poor cleanup of the injected fracture fluid. There are publications studying the clean-up efficiency of hydraulic fractures in vertical wells, however, there is little information in this area for multiple fractured horizontal wells, MFHWs. This paper compares the fracture cleanup efficiency of a hydraulically fractured vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…When the results of these two sets were compared it was observed that the trends of pertinent parameters are more or less similar except for a drop in the magnitude of Pc pertinent parameters. This observation is in line with what was reported previously for high DP VW sets, i.e., in high DP sets the weight of Pc on production improvement was less pronounced (Nasriani and Jamiolahmady, 2018b;Nasriani et al, 2018).…”
Section: Mfhw-sets With Different Dp Valuessupporting
confidence: 93%
See 2 more Smart Citations
“…When the results of these two sets were compared it was observed that the trends of pertinent parameters are more or less similar except for a drop in the magnitude of Pc pertinent parameters. This observation is in line with what was reported previously for high DP VW sets, i.e., in high DP sets the weight of Pc on production improvement was less pronounced (Nasriani and Jamiolahmady, 2018b;Nasriani et al, 2018).…”
Section: Mfhw-sets With Different Dp Valuessupporting
confidence: 93%
“…It was noticed that if the formation becomes tighter (smaller k m ), it results in a more substantial loss in the gas production and consequently, the cleanup procedure will become slower and vice versa. It was also concluded that if the pressure drawdown is small, the impact of Pc on the clean-up performance was more significant, a similar observation was noted once the soaking time was extended (Nasriani, 2017;Nasriani et al, 2018, 2014b, 2014a, Nasriani and Jamiolahmady, 2018a, 2018b. Nasriani et al (2018) captured the impact of injected fracture fluid volume, length of the fracture, pressure drawdown, hysteresis, layering, gravity segregation and mobility/immobility of the formation water on the post-fracturing cleanup performance.…”
Section: A N U S C R I P Tmentioning
confidence: 80%
See 1 more Smart Citation